2017
DOI: 10.1093/ee/nvx156
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Apanteles hemara (Hymenoptera: Braconidae) on two Amaranth Leaf-webbers: Spoladea recurvalis and Udea ferrugalis (Lepidoptera: Crambidae)

Abstract: Amaranth is an African indigenous vegetable that is gaining popularity due to its nutritional, medicinal, and economic values. In East Africa, frequent outbreaks of Lepidopteran leaf-webbers, Spoladea recurvalis F. (Lepidoptera: Crambidae) and Udea ferrugalis Hübner (1976) are reported on this crop, causing up to 100% foliage loss. The larval endoparasitoid Apanteles hemara Nixon is also frequently found associated with these pests during the outbreaks, however, its performance on both pests has never been doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…This is in line with Othim et al. () who reported that experience can increase the responsiveness of Apanteles hemara Nixon (Hymenoptrea: Braconidae) on S. recurvalis and U. ferrugalis .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in line with Othim et al. () who reported that experience can increase the responsiveness of Apanteles hemara Nixon (Hymenoptrea: Braconidae) on S. recurvalis and U. ferrugalis .…”
Section: Discussionsupporting
confidence: 91%
“…Host larval mortality in the presence and absence of the parasitoid were calculated as described by Othim et al. ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dropping to the ground using the silk thread to avoid parasitoid attack is a typical defensive behaviour in many lepidopteran larvae: Udea ferrugalis (Hübner) (Lepidoptera: Crambidae) and Spoladea recurvalis (F.) (Lepidoptera: Crambidae) exposed to Apanteles hemara Nixon (Hymenoptera: Braconidae) (Othim et al., ) and Plutella xylostella (L.) (Lepidoptera: Plutellidae) larvae exposed to Diadegma semiclausum Helen (Hymenoptera: Ichneumonidae) and C. plutellae (Wang & Keller, ) display the same behaviour. The strategy used by C. icipe which involved pursuing the host pest has been reported in C .…”
Section: Discussionmentioning
confidence: 99%